STEM Trails: Enhancing STEM Education through Math Trails with Digital Technology - Cahyono, Adi Nur; Dewi, Nuriana Rachmani; Asih, Tri Sri Noor; Arifudin, Riza; Aditya, Rozak Ilham; Maulana, Bagus Surya; Nugroho, Muhammad Andi (Kreano, Jurnal Matematika Kreatif-Inovatif, 2024)
This study aims to explore the development of STEM Trails to improve STEM Education through the integration of Math Trails activity with Digital Technology. An exploratory study initiative engaged researchers, teachers, students, and programmers. Data was collected through discussions and observations and then evaluated to create STEM Education through Math Trails utilizing Digital Technology. The study demonstrated the successful development of STEM Trails, comprising the STEM Trails platform and the creation of STEM Education activities utilizing Math Trails on the platform. STEM Trailblazers create paths with goals focused on science, technology, engineering, and mathematics using elements found in the surroundings. The trail and tasks are posted on a website for STEM Trail walkers to access and investigate via an application. STEM Trails enable the comprehensive exploration of science, technology, engineering, and mathematics through physical or virtual means. The study suggests that STEM Trails can serve as a mathematics learning approach that mixes outdoor activities with digital technologies and incorporates other subjects. Math Trails is a traditional concept that has been innovatively combined with digital technologies and diverse activities. This method must be broadened and refined by adjusting to the specific circumstances, conditions, and requirements, and then executed in different settings. Penelitian ini bertujuan untuk mengeksplorasi pengembangan STEM Trails untuk meningkatkan STEM Education melalui integrasi aktivitas Math Trails dengan Digital Technology. Sebuah inisiatif penelitian eksploratif melibatkan peneliti, guru, siswa, dan programmer. Data dikumpulkan melalui diskusi dan pengamatan dan kemudian dievaluasi untuk menciptakan STEM Education melalui Math Trails menggunakan Teknologi Digital. Studi ini menunjukkan keberhasilan pengembangan STEM Trails, yang terdiri dari platform Stem Trails dan penciptaan kegiatan STEM Education menggunakan Math Trails di platform tersebut. STEM Trailblazers menciptakan jalur dengan tujuan yang berfokus pada ilmu pengetahuan, teknologi, teknik, dan matematika menggunakan elemen yang ditemukan di sekitarnya. Trail dan tugas diposting di situs web untuk STEM Trail walker untuk mengakses dan menyelidiki melalui aplikasi. STEM Trails memungkinkan eksplorasi komprehensif ilmu pengetahuan, teknologi, teknik, dan matematika melalui sarana fisik atau virtual. Studi ini menyarankan bahwa STEM Trails dapat berfungsi sebagai pendekatan pembelajaran matematika yang menggabungkan kegiatan outdoor dengan teknologi digital dan mengintegrasikan mata pelajaran lainnya. Math Trails adalah konsep tradisional yang telah digabungkan secara inovatif dengan teknologi digital dan berbagai kegiatan. Metode ini harus diperluas dan disempurnakan dengan menyesuaikan dengan keadaan, kondisi, dan persyaratan tertentu, dan dijalankan dalam pengaturan yang berbeda.